Multisystem embolism in hereditary protein C deficiency with patent foramen ovale: a case report - Chen, Lihua; Guan, Jianhua; Ni, Yunfeng (Frontiers in Cardiovascular Medicine, 2025)
Hereditary protein C deficiency (HPCD) is a rare autosomal dominant thrombophilia caused by PROC gene mutations, predisposing patients to venous thrombosis. Patent foramen ovale (PFO) with right-to-left shunt (RLS) may facilitate paradoxical embolism, increasing the risk of stroke and pulmonary embolism. However, the coexistence of HPCD and PFO leading to multisystem embolism has not been previously reported. We report a 29-year-old woman presenting with sudden-onset altered consciousness. The patient had no traditional cerebrovascular risk factors other than oral contraceptive use. Imaging revealed basilar artery occlusion, left pulmonary embolism, and bilateral iliac vein thrombosis. Laboratory testing demonstrated reduced protein C activity, and genetic analysis identified a heterozygous pathogenic PROC variant (c.541T>G, p.Phe181Val). Transcranial Doppler bubble study, transesophageal echocardiography (TEE), and agitated saline contrast echocardiography (ASCE) confirmed a PFO with grade 3 RLS. The patient was diagnosed with HPCD combined with PFO. She underwent emergent mechanical thrombectomy, inferior vena cava (IVC) filter placement, subsequent PFO closure, and lifelong rivaroxaban therapy. At 1-year follow-up, she exhibited excellent clinical recovery with complete resolution of symptoms and no evidence of recurrent thromboembolic events. This first-reported case highlights the potential synergistic thrombotic risk of coexisting HPCD and PFO. For patients with unexplained multisystem embolism, thorough evaluation of both conditions is essential, and individualized comprehensive treatment strategies are crucial for a good prognosis.